Kajian Algoritma Modul Pencetakan Pembimbing Akademik Jurusan Ilmu Komputer - Dwi Sakethi; Didik Kurniawan; Choiranti Efrina (Jurnal Komputasi, 2015)
The list of academic advisor utility is an utility that was developed to help the administration process of computer science major. Previously, it's only used bubble sort sorting algorithm. We try to compare the bubble sort algorithm with selection sort and quick sort to determine the quickest algorithm which will be implemented in other major by searching the worst case (slowest execution time per unit) and best case (fastest execution time per unit). The result is quick < selection < bubble. Selection sort algorithm is proven to be the quickest when n < 26. But the  cademic advisor data that are used in the utility is more than 26. So in this research, the quicksort algorithm is the fastest algorithm.